2021
DOI: 10.1093/humrep/deab067
|View full text |Cite
|
Sign up to set email alerts
|

The use of expanded carrier screening of gamete donors

Abstract: STUDY QUESTION What are the sperm and egg donor rejection rates after expanded carrier screening (ECS)? SUMMARY ANSWER Using an ECS panel looking at 46/47 genes, 17.6% of donors were rejected. WHAT IS KNOWN ALREADY The use of ECS is becoming commonplace in assisted reproductive technology, including testing of egg and sperm donors. Most national guidelines re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Many recipients and regulators seem to start from the premise that sperm banks should guarantee zero risk. One of the prime examples of this belief is the introduction of mandatory expanded carrier screening for donors (Payne et al, 2021). The gain in risk reduction of ECS is minimal (below 1%) (Pennings, 2020).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Many recipients and regulators seem to start from the premise that sperm banks should guarantee zero risk. One of the prime examples of this belief is the introduction of mandatory expanded carrier screening for donors (Payne et al, 2021). The gain in risk reduction of ECS is minimal (below 1%) (Pennings, 2020).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Current American College of Medical Genetics and Genomics guidelines in these cases recommend X-ALD testing be offered to “all pregnant patients and those planning a pregnancy” because of the X-linked inheritance pattern and the prevalence of greater than 1/40,000(3). A recent study demonstrated that expanded carrier screening of gamete donors led to the rejection of 17.6% of donors ( 19 ). Roughly half of those rejected carried 1 of the 4 conditions that American Society for Reproductive Medicine guidelines specifically advise should be required or specifically considered for all gamete donors; however, the remaining variants identified in prospective donors would not have been detected based on current screening recommendations ( 2 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that expanded carrier screening of gamete donors led to the rejection of 17.6% of donors ( 19 ). Roughly half of those rejected carried 1 of the 4 conditions that American Society for Reproductive Medicine guidelines specifically advise should be required or specifically considered for all gamete donors; however, the remaining variants identified in prospective donors would not have been detected based on current screening recommendations ( 2 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIV, hepatitis B virus (HBV), Chlamydia trachomatis according to the screening guidelines listed above) and for genetic screening. The Cryos approach to genetic screening of sperm donors has been published recently ( Payne et al , 2021 ) and in 2018 and 2019 included testing for 46 recessive disorders. Applicants who passed the genetic and infectious diseases screening and completed the relevant consent forms were invited to start donating.…”
Section: Methodsmentioning
confidence: 99%